Interpreting statistical findings : a guide for health professionals and students - Walker, Jan, 1946-; Almond, Palo. (Maidenhead, England : McGraw Hill, 2010)
This text provides support for those conducting literature-based projects which require the student to review evidence generated through empirical investigations. Working from practical examples, exercises and illustrations, explanations will be given in straightforward conceptual terms.
Keywords: Statistics as Topic -- methods